EXPLORING THE RELATIONSHIP BETWEEN PLANT HEIGHT AND YIELD-CONTRIBUTING ATTRIBUTES OF WHEAT IN DROUGHT CONDITIONS - JAVED, HM; NAEEM, A; SHAUKAT, S; MAKHDOOM, M; GHAFOOR, I; SHAHZADI, N; HUSSAIN, F; TIPU, ALK; IMRAN, M; REHMAN, A; MAJEED, T; AKBER, AR (Biological and Clinical Sciences Research Journal, 2024)
Plant height is the most dynamic yield-affecting trait which has strong genetic and phenological associations with yield performance in wheat. The objective of the study was to explore the effect of plant height on spike yield by investigating the interrelationship between height and yield components of ninety wheat genotypes under a drought environment. Different statistical procedures including correlation, regression, path coefficient, principle component, biplot, and cluster analysis were performed to dissect the associative role of height and yield components in setting the yield potential of wheat plants. High positive correlation and direct effects are seen for spike yield from seed weight (r = 0.73) and seed number (r = 0.60) with a participatory contribution of 58% and 40%, respectively. But plant height is negatively associated with thousand seed weight (-0.22*) and spike yield (-0.15) in such a way that each additional unit (1cm) of height reduces 0.11 g thousand seed weight and 0.06 g spike yield due to negative regression. PC1 and PC2 associate height and yield components respectively and both types of traits moderately oppose each other for simultaneous improvement. Highly tall and short plants were observed with low yield potential under water-limited resources due to strong negative effects either on seed weight or number. An increase in height favors seed number but reduces enough seed weight to cause comparative losses. Intelligent allocation of plant resources to height or spike defines the plant yield potential. Plants with moderate height ranging from 74-83 cm were seen with the best yield potential among five different classes of height. Genotypes HM729, HM829, and HM644 belonged to this class and their better yield potential was due to the balance ratio of seed weight and number. This work would help direct our breeding programs for the improvement of the height-oriented yield potential of wheat.